Analisis Pengaruh Faktor Internal dan Eksternal terhadap Praktik Audit Independen di Inspektorat dan BPKAD Kota Binjai - Siti Rahma Dani; Etty Harya Ningsi; Fhikry Ahmad H. Siregar (AKUNTOTEKNOLOGI : JURNAL ILMIAH AKUNTANSI DAN TEKNOLOGI, 2024)
The Inspectorate is an element of supervision of local government administration led by the Inspector whose position is below and responsible to the Mayor/Regent through the Regional Secretary. The Binjai City Regional Finance and Asset Management Agency has the task of carrying out several regional authorities in the financial sector, as well as carrying out other duties in accordance with the policies set by the Mayor based on applicable laws and regulations. The regional inspectorate is one of the units that conducts audits of local governments. In carrying out its main duties and functions, the City/Regency Inspectorate conducts routine inspections of all Regional Apparatus Organizations in each City/Regency. The audit process is important to ensure the accountability of local government financial statements. In the government, both central and regional, there are internal audits and external audits. The internal auditor of the local government is the Inspectorate, while the external auditor of the local government is the Regional Financial and Asset Management Agency. The phenomenon in Indonesia, especially in local governments, is that very few local government financial statements receive fair records without exception from BPKAD. This study aims to find out and analyze whether internal factors have a significant effect on the practice of independent audit in the Binjai City Inspectorate, to find out and analyze whether external factors have a significant effect on the practice of independent audit in the Binjai City BPKAD and to find out and analyze whether internal and external factors have a simultaneous effect on the practice of independent audit in the Binjai City Inspectorate and BPKAD. used is quantitative research, which emphasizes analysis on numerical data (numbers) processed with statistics. With the quantitative method, the significance of group differences or the significance of the influence between the variables studied will be obtained. The results of the analysis showed that (1) there was a significant influence between internal factors and independence at the significance level of 5% with a coefficient of rx1y = 0.535, (2) there was no significant influence between external factors and independence at the significance level of 5% and the correlation coefficient rx2y = -0.161, (3) there was no simultaneous influence between internal factors and external factors with independence at the significance level of 5% rx1x2y = 0.305.